Comparative efficacy of psychological interventions for internet gaming disorder: a meta-analysis of randomized controlled trials - Wang, Ruofei; Zhang, Yueqian; Liu, Zikang; Dong, Hanwen; Zhang, Zhao; Yang, Kebing; Liu, Yan; Zhao, Rongjiang; Yang, Qingyan; Niu, Yajuan (Frontiers in Psychiatry, 2025)
BackgroundThis study employed a systematic review and meta-analysis to evaluate the efficacy of standalone psychological interventions for internet gaming disorder in randomized controlled trials. It further compared the effectiveness of psychological interventions across domestic and international studies, various intervention modalities, and different intervention durations. The goal is to provide empirical support for optimizing intervention strategies.MethodsA computerized search was conducted to identify randomized controlled trials on psychological interventions for gaming addiction published between 2015 and 2025 in EMBASE, the Cochrane Library, PubMed, CNKI, VIP, and Wanfang databases. Two researchers independently assessed the quality of the included studies and extracted relevant data. Meta-analysis was conducted using Review Manager 5.4 and Comprehensive Meta-Analysis Version 3. Subgroup analyses were performed with region, intervention modality, and intervention duration as moderator variables. A random-effects model was used to estimate the overall effect size. Heterogeneity among studies and publication bias were assessed.ResultsIn total, six studies were included, involving 372 participants. The results of the meta-analysis indicate that psychological interventions can alleviate symptoms of internet gaming disorder (SMD = -0.06, 95%CI: -0.99 to -0.20, P = 0.003). Subgroup analyses revealed that domestic psychological interventions (SMD = -0.89, 95%CI:-1.25 to -0.52, P < 0.00001), offline interventions (SMD = -0.67, 95%CI: -1.17 to -0.17, P = 0.008), and short-term interventions (SMD = -0.82, 95%CI: -1.27 to -0.37, P = 0.0004) were more effective in treating internet gaming disorder.ConclusionsPsychological interventions demonstrated significant therapeutic effects on internet gaming disorder; Specifically, domestic psychological interventions, offline interventions, and short-term interventions demonstrated superior efficacy compared to foreign interventions, online interventions, and long-term interventions, respectively. However, due to the limited number of included studies and substantial heterogeneity, meta-regression was not conducted; instead, subgroup analyses were employed to explore potential sources of heterogeneity.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251023957.